2004
DOI: 10.1002/ajmg.b.30102
|View full text |Cite
|
Sign up to set email alerts
|

Transmission disequilibrium tests confirm the link between DRD4 gene polymorphism and infant attachment

Abstract: Following up the results of a previous population association study (Lakatos et al. [2000: Mol Psychiatry 5:633-637; Lakatos et al. [2002: Mol Psychiatry 7:27-31]) by analyses based on parental genetic data confirmed the link between infant attachment and the dopamine D4 receptor (DRD4) gene. Extended transmission disequilibrium tests (ETDT) were performed to determine whether biased transmission of exon III 48 basepair repeat alleles occurred to infants displaying disorganized and secure attachment behavior w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 40 publications
2
60
2
1
Order By: Relevance
“…Analysis of the -521 C/T regulatory (promoter) polymorphism of the same gene revealed that the association of the 7-repeat allele and disorganized attachment was observed only in the presence of the -521T allele (Lakatos et al, 2002). While a Dutch study failed to replicate this result in a small twin sample (Bakermans-Kranenburg & van IJzendoorn, 2004), further family-based transmission disequilibrium tests (TDT) in the Hungarian sample have found a highly significant non-transmission of the 7-repeat allele to securely attached infants, as well as a trend for preferential transmission to disorganized infants (Gervai et al, 2005). …”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Analysis of the -521 C/T regulatory (promoter) polymorphism of the same gene revealed that the association of the 7-repeat allele and disorganized attachment was observed only in the presence of the -521T allele (Lakatos et al, 2002). While a Dutch study failed to replicate this result in a small twin sample (Bakermans-Kranenburg & van IJzendoorn, 2004), further family-based transmission disequilibrium tests (TDT) in the Hungarian sample have found a highly significant non-transmission of the 7-repeat allele to securely attached infants, as well as a trend for preferential transmission to disorganized infants (Gervai et al, 2005). …”
Section: Introductionmentioning
confidence: 92%
“…Control for genetic stratification-In the ethnically homogeneous Hungarian sample, DRD4 genotypes in both the infant and the parental groups were in Hardy-Weinberg equilibrium, reflecting a random combination and stable frequencies of the DRD4 repeat alleles in this population (Gervai et al, 2005;Lakatos et al, 2000). For the ethnically heterogeneous US sample, 40 random marker polymorphisms distributed evenly along the human genome (1-3 markers per chromosome) were analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…117,[160][161][162][163][164][165] As we first noted, 164,165 the study of temperament traits in children offers the opportunity to study gene effects at a time in development when environmental effects are conjectured to be minimal and genetic associations might be more robustly demonstrated.…”
mentioning
confidence: 99%
“…Gervai et al (2005) Bakermans-Kranenburg & van Ijzendoorn, 2004;Gervai et al, 2007;Lee Raby et al, 2013;Luijk et al, 2011;Spangler et al, 2009; Strangely, Luijk et al (2011) actually found opposite trends in each cohort. In the American cohort, infants without the 7R allele developed higher levels of security if their mother was more sensitive but in the Dutch cohort, the trend was in the opposite direction.…”
Section: Attachment Disorganization and The Dopamine D4 Receptor Genementioning
confidence: 97%